On the distribution of energy versus Alfvénic correlation for polar wind fluctuations - B. Bavassano; R. Bruno (Annales Geophysicae, 2006)
Previous analyses have shown that polar wind fluctuations at MHD scales appear as a mixture of Alfvénic fluctuations and variations with an energy imbalance in favour of the magnetic term. In the present study, by separately examining the behaviour of kinetic and magnetic energies versus the Alfvénic correlation level, we unambiguously confirm that the second population is essentially related to a large increase of the magnetic energy with respect to that of the Alfvénic population. The relevant new result is that this magnetic population, though of secondary importance in terms of occurrence frequency, corresponds to a primary peak in the distribution of total energy. The fact that this holds in the case of polar wind, which is the least structured type of interplanetary plasma flow and with the slowest evolving Alfvénic turbulence, strongly suggests the general conclusion that magnetic structures cannot be neglected when modeling fluctuations for all kinds of wind regime.